2016
DOI: 10.1186/s13550-016-0192-9
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of cyclooxygenase-2 (COX-2) in a pre-clinical colorectal cancer model

Abstract: BackgroundCyclooxygenase-2 (COX-2) is the inducible isoform of the cyclooxygenase enzyme family. COX-2 is involved in tumor development and progression, and frequent overexpression of COX-2 in a variety of human cancers has made COX-2 an important drug target for cancer treatment. Non-invasive imaging of COX-2 expression in cancer would be useful for assessing COX-2-mediated effects on chemoprevention and radiosensitization using COX-2 inhibitors as an emerging class of anti-cancer drugs, especially for colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 32 publications
2
49
0
1
Order By: Relevance
“…Interestingly, in majority of mice radiotracer accumulation in A2058 tumor was more pronounced in the peripheral zone of the tumor (tumor rim) compared to the tumor core (Figure B), a phenomenon already observed by Tietz et al …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, in majority of mice radiotracer accumulation in A2058 tumor was more pronounced in the peripheral zone of the tumor (tumor rim) compared to the tumor core (Figure B), a phenomenon already observed by Tietz et al …”
Section: Resultssupporting
confidence: 74%
“…also observed 43 % of radioactivity in blood cells at 60 min p.i. using the methylsulfonyl substituted [ 18 F]pyricoxib . Further metabolite analysis in urine and feces revealed that [ 18 F] DHPI was excreted in form of at least three more hydrophilic radioactive metabolites (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Shukuri et al studied 11 C-ketoprofen methyl ester, which has 62-fold higher selectivity for COX-1 than for COX-2, in rodents and humans (8)(9)(10); however, this agent is confounded by quantitation issues for the radiolabeled prodrugs, making it difficult to distinguish whether radioactivity is retained in brain because of high-affinity binding to COX-1 or merely by trapping of the negatively charged acid. With regard to PET radioligands for COX-2, no results have been published from human or nonhuman primates, although a few candidate radioligands have been studied in rodent inflammation models (11)(12)(13).…”
mentioning
confidence: 99%
“…Toward this end, our laboratory recently developed 2 PET radioligands, 11 C-PS13 ( 11 C-1,5-bis-(4-methoxyphenyl)-3-(2,2,2-trifluoroethoxy)-1H-1,2,4-triazole) and 11 C-MC1 ( 11 C-6-methoxy-2-(4-(methylsulfonyl)phenyl)-N-(thiophen-2-ylmethyl)pyrimidin-4-amine), which are potent and selective for COX-1 and COX-2, respectively ( Fig. 1) (14)(15)(16).…”
mentioning
confidence: 99%
“…Weiterhin wurden 18 F-und 11 C-markierte Substanzen entwickelt, deren In-vivo-Stabilität und Lipophilie entweder mangelhaft war oder deren Bindung keine hohe Affinität und Selektivität für die Zielstruktur zeigte [77]. Hier wurde aktuell ein neuer fluorierter Tracer entwickelt ( 18 F-Pyricoxib), der im Tiermodell die geforderten Eigenschaften erfüllt [65,142].…”
Section: Visualisierung Von Komponenten Des Arachnidonsäure-metabolismusunclassified